The symptomatology and diagnosis of domoic acid toxicosis in stranded California sea lions (Zalophus californianus): a review and evaluation of 20 years of cases to guide prognosis - McClain, Abby M.; Field, Cara L.; Norris, Tenaya A.; Borremans, Benny; Duignan, Pàdraig J.; Johnson, Shawn P.; Whoriskey, Sophie T.; Thompson-Barbosa, Lorraine; Gulland, Frances M. D. (Frontiers in Veterinary Science, 2023)
Domoic acid (DA) is a glutaminergic excitatory neurotoxin that causes morbidity and mortality of California sea lions (Zalophus californianus; CSL) and other marine mammals due to a suite of effects mostly on the nervous and cardiac systems. Between 1998 and 2019, 11,737 live-stranded CSL were admitted to The Marine Mammal Center (TMMC; Sausalito, CA, USA), over 2,000 of which were intoxicated by DA. A plethora of clinical research has been performed over the past 20 years to characterize the range of toxic effects of DA exposure on CSLs, generating the largest dataset on the effects of natural exposure to this toxin in wildlife. Here we review published methods for diagnosing DA intoxication, clinical presentation and treatment of DA-intoxicated CSL, and present a practical, reproducible scoring system called the neuroscore (NS) to help assess whether a DA-affected CSL is fit for release to the wild following rehabilitation. The largest proportion of DAintoxicated CSL were adult females (58.6%). The proportions of acute and chronic cases were 63.5% and 36.5%, respectively, with 44% of affected CSL released and 56% either dying naturally or euthanized. The average time in rehabilitation was 15.9 days (range 0-169) for all outcomes. Logistic regression models were used to assess the relationships between outcome (released vs. euthanized or died) and multiple variables to predict the outcome for a subset of 92 stranded CSLs. The best 2 This is a provisional file, not the final typeset article performing model (85% prediction accuracy; area under the curve = 0.90) consisted of four variables: final NS, change in NS over time, whether the animal began eating in rehabilitation, and the state of nutrition on admission. These results suggest that a behavioral scoring system is a useful tool to assess the fitness for release of stranded DA-intoxicated CSL.